Pursuing an early extension of New Start: Evaluating the decision space for the Obama administration and its successor. Issue 5 (19th October 2016) - Florick, Davis
ABSTRACT: With rumblings that the Obama administration is considering an early extension to the New Strategic Arms Reduction Treaty, it is important to review the advantages and disadvantages to extending the treaty at this time. Moreover, in light of Russia's strategic and nonstrategic nuclear weapon investments, as well as its broader, destabilizing foreign policy, there are plenty of reasons to delay. Conversely, the transparency the treaty provides and the strategic ceilings it institutes have a special value unto their own. Pursuing an extension now is not in the best interests of the United States, while examining other policy options is prudent.